6(2x-12)=8(2x-16)

Simple and best practice solution for 6(2x-12)=8(2x-16) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(2x-12)=8(2x-16) equation:


Simplifying
6(2x + -12) = 8(2x + -16)

Reorder the terms:
6(-12 + 2x) = 8(2x + -16)
(-12 * 6 + 2x * 6) = 8(2x + -16)
(-72 + 12x) = 8(2x + -16)

Reorder the terms:
-72 + 12x = 8(-16 + 2x)
-72 + 12x = (-16 * 8 + 2x * 8)
-72 + 12x = (-128 + 16x)

Solving
-72 + 12x = -128 + 16x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-16x' to each side of the equation.
-72 + 12x + -16x = -128 + 16x + -16x

Combine like terms: 12x + -16x = -4x
-72 + -4x = -128 + 16x + -16x

Combine like terms: 16x + -16x = 0
-72 + -4x = -128 + 0
-72 + -4x = -128

Add '72' to each side of the equation.
-72 + 72 + -4x = -128 + 72

Combine like terms: -72 + 72 = 0
0 + -4x = -128 + 72
-4x = -128 + 72

Combine like terms: -128 + 72 = -56
-4x = -56

Divide each side by '-4'.
x = 14

Simplifying
x = 14

See similar equations:

| 6x+5=-5+2x+26 | | 3a^2+xa=x^2 | | -9-x=7 | | -4x-4(x+14)=-136 | | 6(2-t)-(3-4t)=2 | | 4=4-6r-7r | | 2y=5(4)-12 | | 12x-4x=-40 | | 104-7x=20x+17 | | 3x+3(3x-15)=39 | | 13-7x=38-14x | | 8(x-9)=6(2x-12)-4x | | 45x^2+10x-0.2=0 | | x+9=-3x+11 | | x^3-5x^2+6x+2=0 | | v-15=-2 | | 5(1270)+(1270)=7620 | | ln(7x+12)-ln(x)=ln(8) | | 5(y-1)=3y+9 | | 428=2*84+40*h | | 25+75x=925 | | 5(2x-4)+6X= | | 4(6-2m)-m= | | -3x^4-3x^2+1=0 | | 10-2x=32 | | 2(6y+6)+10= | | -3(y+2)=2(y+6)+7 | | 9(r+2)-4r= | | 2(5z-5(2z-3))=4z-12 | | 0.6m+2=10 | | 4(5-t)-(3-2t)=10 | | -3(-9x+6)-7x=5(x-4)-4 |

Equations solver categories